The production of fly ash aggregates - Nur Amalina Ahmad (Universiti Malaysia Perlis, 2009)
This aim of study is to characterize the physical properties manufactured aggregates that produces from waste, which is fly ash. In this study an attempt has been made to find the suitability of the fly ash waste and reinforced by kaolin and cement as a possible replacement for the conventional aggregates as coarse aggregates. Following the series of raw material mixture, 12 samples of aggregates were manufacture to find the suitable mixing of raw material for producing the required aggregates properties. The palletizing process using the palletizing machine conducted the manufacturing step. This thesis involves a comparative analysis in water absorption and bulk density measurement for the aggregates. After the basic physical properties were establish a micro analysis by using Scanning Electron Analysis were carried for the two samples A8 and A10 because of their better properties and followed by Energy Dispersion Spectrometer for chemical composition investigation. Samples A8 and A10 were then use in testing for concrete. Finally, the results of compressive strength of the cube of concrete were analyzed to determine the strength and hardness of the manufactured aggregates.